Perbandingan Open Spike dan Quick Spike pada Proliga Tahun 2024 Ditinjau Dari Tingkat Keberhasilan Tim Melalui Analisis Video - Dewi, Putri Arista; Jariono, Gatot; Sestiasih, Vera Septi; Nurhidayat, Nurhidayat (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine the comparison of open spikes and quick spikes in the 2024 Pro League in terms of team success levels through video analysis. The type of research method the author uses is quantitative with descriptive analysis methods. This research was carried out at the Muhammadiyah University of Surakarta. Jalan Ahmad Yani, Mendungan, Pabelan, Kec. Kartasura, Sukoharjo Regency, Central Java 57162. The research was carried out on 23 September 2024 – 30 September 2024. The population in this study was the teams competing in the 2024 Proliga with a total of 14 teams with 7 men's teams and 7 women's teams. The sample in the research consisted of 2 men's teams, namely Jakarta Lavani Allo Bank and Jakarta Bhayangkara Presisi, as well as 2 women's teams, Jakarta BIN and Jakarta Electric PLN, who competed in the 1st place final on July 21, 2024. In this study, data analysis techniques were used using The percentage formula is a way to calculate the ball entering the open spike and quick spike when the match uses values. Through a video analysis approach, researchers will summarize data from the final match for 1st place for the men's team between Jakarta Bhayangkara Presisi Vs Jakarta Lavani Allo Bank and the women's team between Jakarta Electric PLN Vs Jakarta BIN, thereby producing a comprehensive and accountable analysis. The conclusion is that both open spikes and middle blockers have a significant level of success in the context of the game, but the effectiveness of each technique varies depending on the game situation and the opponent's strategy. Keywords: strategy, open spike, quick spike, team success